SISTEM INFORMASI LAPORAN ARUS KAS MENGGUNAKAN DIRECT METHOD PADA BMT AMANAH WELERI - Munifah; Miftahurrohman; Rifadhiyah Hikmah (Elkom: Jurnal Elektronika dan Komputer, 2023)
BMT Amanah Weleri is a sharia financial institution engaged in service companies. BMT Amanah began operating in 2006 which is located in Kec. Weleri, Kab. Kendal. In its activities, BMT Amanah Weleri every month cannot be separated from making Cash Flow reports, to support it, a good computerized system is needed for the smooth performance of BMT Amanah. Based on surveys and observations of the BMT Amanah Weleri Cash Flow Information System, financial reporting still uses a manual system so it takes longer to process the recording, this is felt to be less effective because there is no adequate information system. where each company's cash receipts will be recorded by the finance department which will later be recapitulated in the annual report and juxtaposed with other recording results such as cash disbursements. With a cash flow information system at BMT Amanah Weleri, it makes the process of recording and inputting data easier and minimizes errors. The existence of an information system is also able to produce cash flow reports more quickly, precisely and accurately.